PENGKAJIAN TENTANG PENYUSUNAN DAN PENYAJIAN LAPORAN KEUANGAN PADA LEMBAGA KEUANGAN SYARIAH - Diana Fajarwati; S. Djoko Sambodo (JRAK: Journal of Accounting Research and Computerized Accounting, 2010)
The main objective of this research are to study how the sharia institutions in preparing financial statement and to review the component of it’s financial statement are in accordance with general accepted accounting principles in Indonesia. The descriptive evaluation method was used in this research and supported by questionnaires , observation, documentations and triangulation technique in collection of data. The result of this research could be disclosed that there are three sharia institutions have prepared financial statement and of it’s component are in accordance with the general accepted accounting principles in Indonesia, such as: (1) Balance sheet, profit and loss statement, statement of changes in equity, cash flow statement, statement of changes in ZIS funds, and statement of changes in bound investment fund, for the year 2006 – 2007.